FRAÇÕES OXIDÁVEIS DE CARBONO ORGÂNICO DO SOLO EM SISTEMA SILVIPASTORIL - OLIVEIRA, Izadora Araújo; SILVA, Aline Nunes da; ENSINAS, Simone Cândido; BARBOSA, Giselle Feliciani; MACHADO, Isabela (ANAIS DO ENIC, 2020)
-